Application of the genetic algorithm in determining compensating capacitors sizing for loss minimization in power system / Saodah Omar - Omar, Saodah (2003)
This report present the applications of genetic algorithm in determining compensating capacitors sizing for loss minimization in power system. The proposed technique was tested on a 6-bus system and a genetic algorithm programmer was developed using Borland C++ programming language. The developed GA is to determined the size of the compensating capacitors located at the load buses with an objective to minimize the transmission losses. From the results it shows that the proposed technique is able to determine the suitable size of the compensating capacitors in order to minimize the losses in the system.